Cylindrical macrocyclic compounds synthesized by connecting two bowl-shaped calix[3]aramide moieties: structures and chiroptical properties. Issue 57 (18th September 2020) - Sakagami, Ryoko; Saito, Yuuki; Mori, Ryuichi; Satake, Misa; Okayasu, Misaki; Kikkawa, Shoko; Hikawa, Hidemasa; Azumaya, Isao
Abstract : Chiral macrocyclic compounds whose absolute configurations were derived from the amide bond direction were synthesized by homo coupling of meta -calix[3]aramide derivatives. Abstract : Calix[3]aramide-based macrocycles 1 were successfully synthesized by a Glaser coupling reaction of two meta -calix[3]aramide moieties that have three ethynyl groups. The obtained macrocycles have stereoisomers: an enantiomeric pair and a meso form based on a combination of amide bond directions in the calix[3]aramide moieties at both ends of the molecule. Characteristic absorption spectra derived from the 1, 4-diphenylbutadiyne structure were observed, while their ECD spectra were mirror-images. Single-crystal X-ray analysis revealed that each stereoisomer had a cylindrical rigid shape, and the absolute structure of the chiral-form was also assigned by comparing the Flack parameters. Mirror-image VCD spectra were observed for the enantiomeric chiral forms, and a VCD signal pattern of one enantiomer corresponded to that predicted by the relationship between the dihedral angle of the pair of CO groups.